(untitled) - Neubeck, Kenneth J. (Botton, MA, 2005)
This is the introductory sociology text that shows students how sociology is relevant in their daily lives. Sociology, 12/e, has an innovate new design, contemporary and relevant student applications, plus a wealth of supplemental material. This revision elevates Sociology’s high standard of excellence, ensuring that it remains one of the foremost comprehensive introductory sociology resources for students and instructors alike.
Keywords: Sociology,Xã hội học